Properties of CO2 sand brick - Krishnaveni, S; Balaji, P.; Manigandan, R.; Mohamed Haroon, H.; Kesavan, S. (International Journal of Engineering and Technology, 2018)
Brick is the most commonly used building material for construction. The CO2 absorption in the brick manufacturing process can provide a green environment. Therefore, focus should be now on seeking eco – friendly solutions for greener environment. Thus the paper focused on the Carbon di-oxide sand brick which can be manufactured by using carbon di-oxide gas injected into the air tight mould which contains silica sand with sodium silicate and dipping with epoxy resin as a binding agent which provides 2.5 times higher strength than the normal concrete structure in tensile strength and also it requires less reinforcement in place of concrete walls.